MORGAN LLYWELYN’S CELTIC IDENTITY AND THE CELTIC FOLKLORE IN THE ELEMENTALS - ÇETİNER, Niğmet (ASOS Yayinevi, 2020)
Morgan Llywelyn, aka Shannon Lewis, who is an exemplary writer of historical fantasy, historical fiction and historical non-fiction started her writing career thanks to her mother’s encouragement after a disappointing experience and became a prolific writer. She deals with Celtic history, culture, myth and folklore through her novels. Her works reflect her national pride and love of her Celtic roots that reach back to Llywelyn the Great. She discovered her nation’s ancient roots through strenuous efforts of historical research and wrote them down blending fact and fiction through processing archeological and historical evidences with her vivid imagination. In addition to her novels, she has short stories and non-fiction works. Llywelyn’s stories are set in different time frames and they are historically accurate in terms of main events and characters. The aim of this study is first to give biographical information of Morgan Llywelyn along with the manifestations of her Celtic identity. Moreover, the representations of Celtic folklore in her environmental fantasy, The Elementals (1993) shall be explained.